Efektivitas Penerapan Vessel Traffic Services (VTS) di Selat Sunda terhadap Keselamatan Pelayaran - A. Syafaat, Buce; Sukmawati, Eka; Muh. Akib, Irawati; Mayseptyana, Annik; Sugiawiharja, Egi (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2021)
The purpose of this research is to identify the effectiveness of VTS implementation in Sunda Strait and to determine the factors of VTS Merak Station operational staff obstacles in carrying out the work instructions for monitoring and identifying ships disturbances to formulate immediate action in order to ensure the shipping safety. This descriptive method research used qualitative approach by conducting an analysis of the VTS implementation suitability with the regulations at Merak Station. The regulations have been set by the Directorate General of Sea Transportation of the Ministry of Transportation in terms of VTS service SOP documents congruence with operational staff qualifications. The results show that the implementation of the VTS service at Merak Station has been carried out in accordance to the SOP though it is still facing obstacles; shipping companies and ship’s crew who do not fully understand the purpose of applying VTS in Sunda Strait. Moreover, not all VTS staff are certified related to navigational knowledge/skills (eg. VTS certificates) and to Nautical/Technical knowledge/skills (eg. ANT Certificate). Based on the research results, it is recommended that a system to communicate and coordinate should be built between regulators; the Navigation Directorate of the Directorate General of Sea Transportation and stakeholders, to ensure that VTS services at Merak Station could be implemented based on the regulations.